Marketing Strategy: Increasing Consumers Loyalty through Trust in the Halal Certificate and Logo displayed in North Sulawesi Restaurants - Syarifuddin Syarifuddin; Silvya Lefina Mandey; Willem J. F. A. Tumbuan; Joubert B. Maramis (Cita Konsultindo Research Center, 2022)
Religious doctrine is an important element and a strategy to create consumers loyalty. Therefore, this study analyzed the role of healthy eating behaviors, fair prices, food quality, and halal certificate trust as variables of religious doctrine on consumers loyalty to restaurants that display the halal logo in North Sulawesi, Indonesia. The data were collected using questionnaires, which was targeted at Muslim consumers who had visited more than 3 times to obtain a total of 270 respondents. Meanwhile, the hypothesis analysis employed the SEM-AMOS 26 technique. The results showed that healthy eating behaviors and food quality were negatively associated with trust in the halal certificate, while fair prices had a positive relationship. A positive and significant influence on consumers loyalty was also demonstrated by healthy eating behaviors and fair prices but not food quality. Furthermore, healthy eating behavior but not halal certificate trust was found to act as a partial mediator between fair prices and loyalty.